Ending Violence Against Women In Indonesia: State Policy And Practice - Abdul Aziz, Zarizana (2016)
Public international law mandates States to promote protect and fulfil human rights. State obligation at the international level is determined by international law which is comprised in the various treaties a State ratifies as well as customary international law. When a State assumes international obligations, it is obliged to comply with its international obligations premised on the due diligence principle. The research critically analyses the evolution, development and application of the due diligence principle in international law and presents a discourse on its utility in clarifying State obligation to eliminate violence against women. It then investigates Indonesia’s international obligation to end violence against women and what this obligation entails in the island of Java by focusing on specific forms of violence against women and by analyzing how far these efforts are in response to treaty obligations. Finally, the research investigates the perspectives of civil society in the assessment of Indonesia’s efforts, achievements and challenges in fulfilling the obligations and finally identifies and makes recommendations in areas where due diligence may be particularly useful and /or further used in eliminating violence against women.